Sustainable Finance Implementation on Institutional Aspects in Indonesia and the European Union - Asni Mustika Rani; Atih Rohaeti Dariah; Popon Srisusilawati (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Realizing sustainable finance practices towards a zero-carbon emission economy requires support and participation from all stakeholders, especially regulators from an institutional perspective. Sustainable finance is crucial in driving transformative economic growth towards sustainability. This study aims to scrutinizes the appropriate institutional elements that can bolster sustainable finance initiatives within Indonesia and the European Union (EU). Using the content analysis method, this research delves into various written media, regulations, laws, and documents. The study reveals that, from an institutional perspective, both the EU and Indonesia align their sustainable finance implementation with regulators' work plans, characterized by shared goals and objectives. However, technical complexities and evolving regulatory aspects pose challenges, stemming from the need to reconcile diverse political views and adapt to changing circumstances. The results indicate that while strong institutional frameworks and regulatory plans exist, practical implementation of sustainable finance faces hurdles. These include the need for clearer guidelines, enhanced inter-agency coordination, and more robust mechanisms to monitor and enforce compliance. Although sustainable finance initiatives in both regions show promise, continuous improvement and adaptation are essential to effectively contribute to a zero-carbon emission economy.